Hazard analysis and extreme weather mitigation in Pontianak city based on Geographic Information System - Lestari, Nadya Hawa Putri; Jasisca Meirany; Nana Novita Pratiwi; Arfena Deah Lestari; Mochammad Meddy Danial (Teknisia, 2024)
The geographical location of Pontianak City, situated on the Equator, creates a high potential for hydrometeorological disasters, particularly extreme weather events such as whirlwinds. Based on the history of recurring events, it is essential to conduct this research to recommend disaster mitigation strategies based on hazard analysis and the Extreme Weather Disaster Class Index in Pontianak City. The data used are slope, land use, annual rainfall, and surface air temperature. These parameters are processed using the ArcGIS software. The results of the hazard analysis indicate that Pontianak City has a moderate level of hazard, covering an area of 5,191.46 ha, or 44.41% of the total area of Pontianak City. Sub-districts with medium-level potential areas are Pontianak Kota sub-district, with an area of 883.56 ha, West Pontianak sub-district, with an area of 836.97 ha, and South Pontianak sub-district, with an area of 761.59 ha. The non-structural disaster mitigation measures that need to be implemented to reduce the impact of extreme weather disasters include disaster risk assessment, enforcement of mitigation-based spatial plans, and community engagement. While structural mitigation can be achieved by strengthening building structures, these structures must utilize materials and construction techniques that are resistant to whirlwinds and enhance the strength of foundations, walls, and roofs. Making evacuation routes based on disaster mitigation and installing early warning equipment, such as Weather Information Display (WID), also needs to be done in an effort to minimize the impact of extreme whirlwind weather.